Improving employee performance with authentic leadership through job satisfaction - Ahmad Ghoni; Karsikah Karsikah; Didit Haryadi (International Journal of Applied Finance and Business Studies, 2026)
This study analyzes the influence of authentic leadership on employee performance with job satisfaction as a mediating variable in the Dream Wear Cooperative. The research gap can be seen from the inconsistency of previous study results related to the direct influence of authentic leadership on performance, as well as the limited research in the context of cooperatives compared to the banking and manufacturing sectors. This points to the need for more comprehensive testing of mediation models. This study used a causal quantitative approach with 115 respondents through saturated sampling techniques. The analysis was carried out using PLS-SEM SmartPLS 4.1. The results showed that authentic leadership had a significant effect on employee performance (original sample = 0.190, t-stats = 2.387, p = 0.017) and job satisfaction (original sample = 0.311, t-stats = 3.009, p = 0.003). Job satisfaction also had a significant effect on employee performance (original sample = 0.556, t-statistics = 7.475; p = 0.000). These findings confirm that job satisfaction plays an important role as a mediator that strengthens the influence of authentic leadership on employee performance. The novelty of the research lies in the testing of the mediation model in the context of cooperatives which is still rarely researched and the affirmation of the dominance of the role of job satisfaction in explaining the improvement of employee performance.